Praxis Marxist Criticism and Dissent in Socialist Yugoslavia - Sher, Gerson (Indiana University Press, 1977)
From 1964 to 1975 a group of dissident Yugoslav Marxist intellectuals collaborated on, and identified themselves with, the philosophical journal Praxis. In the early 1950s, inspired by the official Yugoslav critique of the Soviet Union and a relaxed cultural atmosphere, they began to develop a radical interpretation of Marxian theory. THese writers maintained that concepts appearing in Marx's early philosophical writings, especially praxis and alienation, formed the lifelong basis for his work of social criticism and remain applicable to all social formations.